Odpowiedzi

2009-12-11T16:34:07+01:00
A.
a1=2
a2=1
q = a2 :a1 = 1 : 2 = ½

a8 = a1*q⁷= 2*(½)⁷
S8 = a1 (1 -q⁸):( 1- q) = 2*[(½)⁸] :( 1-½) = 2*(½)⁸ : (½)= (½)⁻¹*(½)⁸ *(½)⁻¹=
S8 = (½)⁶ = 1/64
S8 = 1/64


b.
a2=3
a3=9

q = a3:a2 = 9 : 3 = 3
a2 = a1*q = 3
a1 *3 =3
a1 = 3:3
a1 = 1
q = 3
S8 = a1 (1 -q⁸):( 1- q) = 1*(1-3⁸) : ( 1- 3) = 1*(1 -3⁸) : (-2 )= -½ *(1-3⁸)
S8 = -½ + ½*3⁸ = -½ + ½*6561 = -½ + 3280½ = 3280

c.
a1=8
a2=-4
q = a2 : a1 = (-4) : 8 = -½
S8 = a1 (1 -q⁸):( 1- q) = 8*[1- (-½)⁸] : [1- (-½)] = 8*[ 1-(-½)⁸] : [1+½]
S8 =8 *[1-(-½)⁸] : (3/2)= 8*[1-(-½)⁸]*(2/3) = (16/3)*[1-(-½)⁸]=
S8 = (16/3)*( 1 -1/256) = (16/3)*(255/126)= 680/63

d.
a2=-1
a3=1
q = a3 : a2 = 1 : -1 = -1
q = -1
a2 = a1*q = -1
a1*( -1) = - 1
a1 = (-1) : (-1) = 1
a1 = 1
q = -1
S8 = a1 (1 -q⁸):( 1- q) = 1*[1-(-1)⁸] : [ 1- (-1)]
S8 = 1*[1- 1] :( +1) =1*0 : 1 = 0
1 5 1